CIVIL LIABILITY FOR DAMAGE ARISING FROM TERRORIST ATTACKS, PUBLIC PROTESTS AND PUBLIC EVENTS - Arsenijević, Bojana (COLLECTION OF PAPERS, FACULTY OF LAW NIŠ, 2025)
The Civil Obligations Act governs civil liability for harm resulting from social conflicts, including terrorist attacks and public protests. Damages incurred at public events are covered under the same legal standard. The state is burdened by strict liability. This case of liability is restricted to specific types of harm brought on by individual death, physical harm, or property destruction. The paper examines the conditions of this liability case, with a focus given to the causal link.Some states that were part of the former SFR Yugoslavia regulate this case of state liability because, upon separation, they enacted laws based on the 1978 federal Civil Obligations Act. Others have abandoned or moderated this case of state liability. A comparable instance for this kind of damage is uncommon in comparative law. The injured party in the criminal acts have the right for compensation, which includes terrorist attacks. In the case of damages during the public protests, state is liable only for the harm that police officers inflict on protesters. With exception to that situation, the rule is that the person who produced the harm is liable for damage caused during public protests, which means that individuals are responsible for any damage they do to other participants during the demonstrations and other public events.
Keywords: Liability for damages from political motivated violence; State liability; Liability for risk; Duty of care and liability for omission